'Legitimacy is the Main Objective': Legitimation in Population-Centric Counterinsurgency. (3rd September 2017) - Kitzen, Martijn
Abstract: This article seeks to contribute to the understanding of the role of legitimacy and different forms of legitimation in population-centric counterinsurgency. An analysis of the logic underlying this counterinsurgency concept sheds a light on the former as it identifies legitimacy as the crucial mechanism through which a collaboration strategy seeks to obtain control over the local population. An exploration of Weber's primary types of legitimate authorities provides the insight that counterinsurgents might operationalize legitimation through either rational-legal ways or by co-opting local power-holders who hold a position as traditional or charismatic leaders. The exact choice of strategy depends on the pattern of legitimacy in the target society and therefore so-called cultural legitimation is pivotal.